Handbook of social and emotional learning - Durlak, Joseph A (The Guilford Press, 2017)
"The burgeoning multidisciplinary field of social and emotional learning (SEL) now has a comprehensive and definitive handbook covering all aspects of research, practice, and policy. The prominent editors and contributors describe state-of-the-art intervention and prevention programs designed to build students' skills for managing emotions, showing concern for others, making responsible decisions, and forming positive relationships. Conceptual and scientific underpinnings of SEL are explored and its relationship to children's and adolescents' academic success and mental health examined. Issues in implementing and assessing SEL programs in diverse educational settings are analyzed in depth, including the roles of school-and district-level leadership, teacher training, and school-family partnerships"